Telecommunications Externality on Migration Evidence from Chinese Villages - Lu, Yi (The World Bank, 2013)
This paper uses a unique natural experiment in Chinese villages to investigate whether access to telecommunications- in particular, landline phones-increases the likelihood of outmigration. By using regional and time variations in the installation of landline phones, the difference-in-differences estimation shows that access to landline phones increases the ratio of out-migrant workers by 2 percentage points, or about 50 percent of the sample mean in China. The results remain robust to a battery of validity checks. Furthermore, landline phones affect outmigration through two channels: information access to job opportunities and timely contact with left-behind family members. The findings underscore the positive migration externality of expanding telecommunications access in rural areas, especially in places where migration potential is large